Pemodelan Sistem untuk Produksi Roti Gepeng pada Roti Gepeng ZB (Zebra Brother) Balikpapan Menggunakan Metode Sistem Dinamis - Hertadi, Christopher Davito Prabandewa; Saputro, Keysha Lovelly Adhara; Yaqin, Alvin Muhammad 'Ainul (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
Bread is a practical source of carbohydrates and is popular among people of all ages, from children to adults. The flatbread factory, "ZB (Zebra Brother)," located in Balikpapan, has been operating since 2004, and its products are pretty well-known to the local community. However, this factory experiences obstacles such as the uncertainty of machine repair times, which impacts the company's ability to reschedule production, and the raw materials provided can exceed their storage period. If all subsystems of the bread production process are well understood, the process can run smoothly and meet market needs. This study aims to identify factors that influence the flat bread production system, analyze and model it to predict production performance over the next 5 years, and provide strategic recommendations to improve and increase the efficiency of the flat bread production system. Of the six scenarios, the five best scenarios were identified, namely adding machines and sales, and conducting regular promotions, which were able to maximize profits and sustainably meet market demand while facing the challenges of increasing raw material prices and growing competition.